Is A-movement a movement? An eye-tracking and self-paced reading investigation - Hudson, Tess (My University, 2020)
In this thesis, I investigate the link between A-movement and online processing in eye-tracking and self-paced reading (SPR). A-movement refers to movement of an element to an argument position, where an element may be base-generated and hold a semantic role of the main predicate of the clause. I analyze six constructions in English, divided into three experimental pairings. Unaccusative constructions argued to involve movement are contrasted with unergatives as control, in a purely intransitive pairing. Transitive verb expectations are controlled by contrasting optional transitive constructions and purported movement in inchoative constructions. Argument alternation is taken into consideration in comparing instrumental constructions and possible movement in middle constructions. The results from the SPR experiment did not show significant differences in reading times or fixation durations between pairings in any regions. In the eye-tracking results, no significant effects were found at the verb region, where the syntactic complexity of movement could lead to greater processing effort. In the subject noun region of the optional transitive and inchoative constructions and instrumental and middle constructions, significant differences in gaze duration, total fixation duration, and go-past time were found. These results are compatible with theories of frequency effects. Differences at the adverb could support lexical or derivational approaches, as controls and experimental conditions had equal length fixations in our first pairing, controls had longer fixations in our second pairing, and experimental items had longer fixations in our third pairing. Ultimately, the results do not offer strong support for the derivational approach, and are not accounted for through a lexical approach.
Keywords: linguistics; theoretical syntax; experimental syntax; eye-tracking; self-paced reading; A-movement